2004
DOI: 10.1070/qe2004v034n09abeh002762
|View full text |Cite
|
Sign up to set email alerts
|

On reasons for strong absorption of light in an optical fibre at high temperature

Abstract: Evaluating the statistical variation of the metal-oxide-semiconductor field-effect transistors (MOSFETs) is important for realizing the accurate analog circuits and highly large-scale-integration (LSI) devices. In this paper, a new evaluation method for the statistical variation of the electrical characteristics of MOSFETs is presented. We have developed the test circuit for understanding the statistical and local variation of MOSFET in very short time. It is demonstrated that a large number of MOSFETs, about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Several hypotheses have been put forward to explain the fiber fuse phenomenon. These include a chemical reaction involving the exothermal formation of germanium (Ge) defects [10], self-propelled self-focusing [3], thermal lensing of the light in the fiber via a solitary thermal shock wave [5], and the radiative collision of SiO and O complexes [32].…”
Section: Introductionmentioning
confidence: 99%
“…Several hypotheses have been put forward to explain the fiber fuse phenomenon. These include a chemical reaction involving the exothermal formation of germanium (Ge) defects [10], self-propelled self-focusing [3], thermal lensing of the light in the fiber via a solitary thermal shock wave [5], and the radiative collision of SiO and O complexes [32].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in the near future the fiber fuse phenomenon will pose a real danger to optical communication systems constructed with conventional single-mode fibers [5]. There have already been many experimental and theoretical reports on the fiber fuse phenomenon [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. In addition, several devices have been proposed with a view to avoiding the catastrophic damage caused by a fiber fuse, for example, a fiber fuse terminator using a tapered fiber [22] and a thermally-diffused expanded core (TEC) fiber [23].…”
Section: Open Accessmentioning
confidence: 99%
“…Therefore, in the near future the fiber fuse phenomenon will pose a real danger to optical communication systems constructed with conventional single-mode fibers [37]. There have already been many experimental and theoretical reports on the fiber fuse phenomenon [20,33,34,36,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. In addition, several devices have been proposed with a view to avoiding the catastrophic damage caused by a fiber fuse, for example, a fiber fuse terminator using a tapered fiber [53] and a thermally-diffused expanded core (TEC) fiber [54] for an input power of not more than 2 W. A device has been reported that can rapidly detect a fiber fuse and terminate it by monitoring the light backreflected from it [55].…”
Section: Applicability To High Power Transmissionmentioning
confidence: 99%